Ultrasound microbubble-mediated delivery of ANLN silencing-repressed EZH2 expression alleviates cervical cancer progression. (August 2022) - Pan, Yanyan; Wei, Min; Gong, Ting
Abstract: Ultrasound-targeted microbubble destruction (UTMD) is a new gene therapy method that uses ultrasound and microbubbles carrying target genes to achieve gene transfection. However, whether UTMD-mediated ANLN silencing transfection helps to restrain the growth of cervical cancer (CC) is obscure. ANLN level in tumor tissues, adjacent tissues, and cells was tested using the database, qRT-PCR, and western blot. The optimal concentration of SF6 was determined by MTT assay. Mechanical index (MI) was selected by flow cytometry. After transfection with liposome or UTMD-mediated liposome, cell function experiments, qRT-PCR, and western blot were employed to assess CC cell biological behaviors and EZH2 level. Epithelial-mesenchymal transition (EMT)-related marker and apoptosis-related marker expressions were examined utilizing qRT-PCR and western blot. 10% SF6 and MI of 0.28 were selected for subsequent tests. ANLN was highly expressed in CC and cells. The transfection efficiency of the UTMD-siANLN group was higher than that of the L -siANLN group. Moreover, the repression of UTMD-siANLN on CC cell malignant phenotypes was stronger than L -siANLN. UTMD-siANLN attenuated EZH2 expression in CC cells. The modulatory role of UTMD-siANLN on EMT- and apoptosis-related markers was reversed by EZH2 overexpression. UTMD can improve the efficiency of siANLN transfection into CC cells to induce suppression of CC cell malignant phenotypes, which may become a new target of gene therapy for CC. Highlights: ANLN was over-expressed in CC tissues and cells. Silencing of ANLN mediated by UTMD hindered the malignant phenotype of CC cells. US-siANLN attenuated EZH2 expression in CC cells. The modulatory role of US-siANLN on EMT- and apoptosis-related markers was reversed by EZH2 overexpression.